Physiological and morphological short-term responses to light and temperature in two Nothofagus species of Patagonia, South America - Varela, Santiago Agustin; Fernandez, María Elena; Gyenge, Javier Enrique; Aparicio, Alejandro Gabriel; Bruzzone, Octavio Augusto; Schlichter, Tomas Miguel (2017)
The study of plant responses to environmental stress factors is essential for management of plant systems and for anticipating their response to climate change. The main goal of this study was to determine morphological and physiological responses of Nothofagus obliqua and N. nervosa seedlings to light and temperature, two of the main stress factors acting in their current natural distribution in NW Patagonia. Responses to light were evaluated analyzing growth and survival, as well as morphological and physiological traits related to them, in seedlings subjected to three contrasting light conditions (full-sun conditions, 50% of sunlight and 20% of sunlight) during one growth season. Temperature photosynthetic responses were evaluated in seedlings subjected to temperature treatments between −5 and 40°C for 2 and 4 h. Growth rate and biomass partition were similar between light treatments in both species. High apical meristem damage and decreased photosynthetic capacity of preformed leaves were observed under full-sun conditions, suggesting that high light levels have a deleterious effect on plant yield. Both species produced neoformed leaves during the growing season with better photosynthetic capacity than preformed leaves under full sun conditions, contributing to plant acclimation. Almost no plasticity was observed in morphological traits in response to shade. Both species differed in optimum temperature for photosynthesis, with a wider temperature range at which high photosynthesis is maintained in N. obliqua. In both species the higher values of net photosynthetic rate were found at higher temperatures than the mean annual temperature of its current natural distribution range. Under no water-stress conditions, future higher temperatures could increase carbon fixation of these species, with a little advantage of N. obliqua if temperature variance is high. Synergy effect of various environmental stress factors, particularly considering cultivation of these species outside their current natural distribution sites require further studies